2005
DOI: 10.1115/1.2370748
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hot-Streaks on HP Vane Surface and Endwall Heat Transfer: An Experimental and Numerical Study

Abstract: Pronounced nonuniformities in combustor exit flow temperature (hot-streaks), which arise because of discrete injection of fuel and dilution air jets within the combustor and because of endwall cooling flows, affect both component life and aerodynamics. Because it is very difficult to quantitatively predict the effects of these temperature nonuniformities on the heat transfer rates, designers are forced to budget for hot-streaks in the cooling system design process. Consequently, components are designed for hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…The generated inlet temperature fields studied by Povey et al (2003) and Povey et al (2007) are quite similar to those found by Li et al (2006), in that the hot streaks are clearly subject to mixing and diffusion, while maintaining their general position near the centre of the flow field as they get convected downstream. These artificially-produced profiles seem to be marginally more coherent and uniform than those produced by an actual combustor, which is likely due to the assumed conditions that have a lower turbulence and a more uniform geometry than those in the actual case.…”
Section: Inlet Temperature Distributionsupporting
confidence: 58%
See 2 more Smart Citations
“…The generated inlet temperature fields studied by Povey et al (2003) and Povey et al (2007) are quite similar to those found by Li et al (2006), in that the hot streaks are clearly subject to mixing and diffusion, while maintaining their general position near the centre of the flow field as they get convected downstream. These artificially-produced profiles seem to be marginally more coherent and uniform than those produced by an actual combustor, which is likely due to the assumed conditions that have a lower turbulence and a more uniform geometry than those in the actual case.…”
Section: Inlet Temperature Distributionsupporting
confidence: 58%
“…Gundy-Burlet and Dorney (1997) simulated hot-streak effects using a hyperbolic-tangent temperature distribution, which also corroborates the general shape of the radial profile. The temperature profile generated in the experiments of Povey et al (2003) and Povey et al (2007) follows a similar parabolic-like trend, as does their comparison data taken from an existing engine.…”
Section: Inlet Temperature Distributionmentioning
confidence: 65%
See 1 more Smart Citation
“…Conversely, hot streaks can have a significant impact on high-pressure vane heat transfer. Povey et al [4] and Qureshi et al [5] demonstrated that the heat transfer rate on the suction side of the vane increases, over the uniform inlet temperature results, when hot streaks are aligned with the leading edge. Conversely, the heat transfer rate over the vane pressure side was found to be insensitive to inlet temperature non-uniformities.…”
Section: Introductionmentioning
confidence: 99%
“…The unsteady flow interactions between the high-pressure turbine and components downstream (an IP or LP turbine) or upstream (combustor) has only been recently published. Experimental studies were conducted on the effect of flow temperature distortions at the turbine inlet section that simulate the presence of an upstream combustion chamber [22,23], hot-streaks effects on the aerodynamics and heat transfer [24,25], hot-streak clocking [26,27]. As modern engine design philosophy places emphasis on higher blade loading and smaller engine length, the effects of unsteady interactions in a multi-row scenario become of utmost interest for turbine designers.…”
Section: Research For Jet Engine Turbinesmentioning
confidence: 99%